The Effect of Compensation System and Career Development on Job Satisfaction in the Retail Industry - Darmadi Darmadi; Suwanto Suwanto (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
High employee turnover in Tangerang City’s retail industry signals dissatisfaction, prompting this study to examine the influence of compensation systems and career development on job satisfaction. The objective is to quantify their individual and combined effects using a quantitative survey approach. Data were collected from 100 retail employees via questionnaires, analyzed through multiple linear regression, instrument testing, and hypothesis testing with SPSS. Results show compensation systems positively affect job satisfaction (β = 0.412, p < 0.05), as does career development (β = 0.378, p < 0.05), with a simultaneous effect (F = 37.214, p < 0.05, R² = 0.427). These findings indicate that fair, transparent compensation and structured career paths significantly enhance employee satisfaction. Practically, retail firms should implement competitive salary structures, performance-based bonuses, and clear promotion pathways to boost loyalty and reduce turnover. The study suggests regular evaluation of these systems to align with market standards and employee expectations, fostering a supportive work environment.